335 Evaluation of Hempseed Cake on Cattle Performance, Carcass Characteristics and Feeding Behavior in Finishing Diets. (8th October 2021) - Winders, Thomas; Serum, Eric; Smith, David J; Neville, Bryan W; Mia, Kafi; Amat, Samat; Dahlen, Carl R; Swanson, Kendall C
Abstract: As cannabinoid production continues to increase, there is increasing interest in feeding byproducts of industrial hemp production to livestock. An experiment using crossbred heifers (n = 31; initial BW= 494 kg, SE = 10) was conducted to determine the effects of feeding hempseed cake in a corn-based finishing diet (10% forage) formulated to meet or exceed ruminally degradable and metabolizable protein requirements on growth, performance, carcass characteristics, and feeding behavior. Heifers were assigned randomly to one of two treatments: 1.) diet containing 20% dried distillers grains plus solubles (CON, n = 16), or 2.) diet containing 20% hempseed cake (HEMP, n = 15) on a dry-matter basis. Cattle were housed in two pens, had ad-libitum access to feed and water, and individual intakes and feeding behavior were captured using the Insentec BV feeding system across the feeding period (111 d). Final BW was not different (P = 0.28) between CON (696 kg, SE = 12) and HEMP (683 kg, SE = 12) heifers. Dry matter intake was not different between treatments (P = 0.99), while CON cattle had improved ADG and feed efficiency (G:F; P ≤ 0.04) compared to HEMP cattle. Carcass characteristics were not different (P ≥ 0.20) between treatments for all parameters measured. Control and HEMP cattle were not different (P ≥ 0.34) for number of meals, time spent eating, number of visits to the bunk per day, meal size, or eating rate. Feeding hempseed cake reduced ADG and G:F while having no effect on other performance measures, carcass characteristics, or feeding behavior. Overall, these data suggest hempseed cake could be a viable alternative feed source for ruminants depending on availability and cost. Further understanding of hempseed cakes' nutrient utilization is critical to determining this products viability as a feedstuff for cattle.